Relationship Between Learning-Related Synaptic and Intrinsic Plasticity Within Lateral Amygdala - (:unkn) unknown (My University, 2015)
A central question in neuroscience is to determine the mechanisms that govern formation, storage and modulation of memories. Determining these mechanisms would allow us to facilitate new memory formation as in the case of aging-related cognitive decline or weaken preexisting pathological memories such as traumatic memories and cue-induced drug craving. Pharmacological and genetic manipulation of intrinsic neuronal excitability has been demonstrated to impact the strength of memory formation, allocation of memories, and modulation of memories through retrieval and reconsolidation-dependent processes. In addition to experimental manipulations of intrinsic excitability, intrinsic plasticity, a change in neuronal intrinsic excitability, can be brought about by behavioral means such as learning. Indeed, learning-related intrinsic plasticity has been observed in many brain structures following acquisition of a variety of learning paradigms. Despite its ubiquitous nature, little is known about the functional significance of learning-induced intrinsic plasticity. Using the well-characterized lateral amygdala-dependent auditory fear conditioning as a behavioral paradigm, the current experiments investigated the time course and relationship between intrinsic and synaptic plasticity. We found that learning-related changes in amygdala intrinsic excitability were transient and were no longer evident 10 days following fear conditioning. We also found that fear learning related synaptic plasticity was evident up to 24hr following fear conditioning but not 4 days later. Finally, we demonstrate that the intrinsic excitability changes are evident in many of the same neurons that are undergoing synaptic facilitation immediately following fear conditioning. These data demonstrate that learning related intrinsic and synaptic changes are transient and co-localized to the same neurons. These data demonstrate that memory encoding neurons are more excitable, thus more likely to capture new memories for a time after the learning event.